The conflict between trade obligations and human rights: a legal analysis of the effects of water privatisation / Aleeya Elyana Ahmad Mahreez … [et al.] - Ahmad Mahreez, Aleeya Elyana; Adam Cho, Elena; Abd Rahim, Nur Allya; Mohamad Redzuan Gunasingam, Nur Allya (2014)
The establishment of the World Trade Organisation (WTO) in 1994 has sparked a new global movement; a forward-moving, economic-growing, finance-generating community in trade. However, being a member of the WTO comes with the consideration to be subjected to a myriad of obligations which would also require countries to lower its own trade barriers as the principical of reciprocity in the WTO so requires it. The WTO has introduced water privatisation, supposedly an ideal concept that water services will be supplied more efficiently when operated by foreign private companies. The supply and distribution of water has always been a public service supplied by the government before the introduction of water privatisation. Under the government, water was usually heavily subsidised making the service in line with the state's obligation to provide its citizens with basic access to water. However, since the WTO mandates water privatisation, it has resulted in exploitation of profit-making company andsuch a phenomena is greatly affecting people's basic right to water and also access to affordable water. This paper will study the current water activities in France, Malaysia and Bolivia to illustrate and compare the varying effects of water privatisation on developed, developing and leastdeveloped countries. Also, this paper will analyse the General Agreement on Trade in Services (GATS), the document where the obligation to privatise water is founded, to observe whether it contains effective mechanism to exempt states from complying with the obligation when public interest and public health is concerned.